2017
DOI: 10.1249/mss.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and Mood Responses to Exercise in Adults with Varying Activity Levels

Abstract: These results indicate that eCB and mood responses to exercise do not differ significantly between samples with varying physical activity levels. This study also demonstrates that in addition to prescribed exercise, preferred exercise activates the eCB system, and this activation may contribute to positive mood outcomes with exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 45 publications
5
72
0
4
Order By: Relevance
“…Consistent with previous research conducted in healthy individuals (Brellenthin et al., ; Koltyn, ), our findings indicate that aerobic exercise was able to elicit improvements in mood as well as reduce pain in healthy adults. Additionally, the results indicated that aerobic exercise was able to elicit significant improvements in mood along with reductions in pain in individuals with PTSD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous research conducted in healthy individuals (Brellenthin et al., ; Koltyn, ), our findings indicate that aerobic exercise was able to elicit improvements in mood as well as reduce pain in healthy adults. Additionally, the results indicated that aerobic exercise was able to elicit significant improvements in mood along with reductions in pain in individuals with PTSD.…”
Section: Discussionsupporting
confidence: 92%
“…For this initial pilot study, we estimated sample size for our primary variable of interest (i.e., eCBs). Based on findings from previous research conducted in our lab (Koltyn et al., ; Brellenthin et al., ) that showed large effect size changes in eCBs following exercise, the analysis was powered at 0.80, with an alpha of .05, and a Cohen's f value of 0.30 (medium effect size). The mixed analysis of variance (ANOVA) power analysis indicated that we would need 12 participants per group ( N = 24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that exercise modulates different endogenous systems, including the eCB system (Tantimonaco et al, 2014). Human studies have demonstrated significant increases in eCBs plasma levels following a single bout of aerobic exercise (Brellenthin, Crombie, Hillard, & Koltyn, 2017;Heyman et al, 2012;Sparling, Giuffrida, Piomelli, Rosskopf, & Dietrich, 2003). However, long-term running significantly reduced plasma AEA levels in mice (Biedermann et al, 2016), while systemic 2-AG administration dose-dependently reduced the wheel revolutions in both obese and lean Zucker rats (Smith & Rasmussen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This question is of theoretical importance to determine whether physical inactivity plays a role in the aetiology of depression. A combination of biochemical and psychosocial factors are likely responsible, including mechanisms through which exercise increases neurogenesis and reduces inflammatory and oxidant markers (Schuch et al, 2016) and activates the endocannabinoid system (Brellenthn et al, 2017). People with depression have reduced hippocampal volumes, fewer markers of neurogenesis (e.g.…”
Section: Discussionmentioning
confidence: 99%